2015
DOI: 10.3947/ic.2015.47.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Accompanying Recent Mycoplasma Infection in a 10-Year-Old Girl

Abstract: Recently, the incidence of pertussis has been increasing; however, reports on mixed infection of pertussis with other respiratory pathogens are rare in highly immunized populations. We report the case of a 10-year-old girl who presented with cough, post-tussive emesis, and fever. She was subsequently diagnosed with bronchopneumonia. Although she had received five doses of diphtheria-tetanus-acellular pertussis vaccine, polymerase chain reaction of her nasopharyngeal aspirate confirmed Bordetella pertussis infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another study in children, although in patients with community-acquired Pneumonia, also have reported coinfections in M. pneumoniae as the most common bacteria detected in association with a virus [39]. Thus, to avoid under-diagnosis, pertussis should be considered in patients with cough, especially if chronic, even when M. pneumoniae have been documented [40].…”
Section: Discussionmentioning
confidence: 99%
“…Another study in children, although in patients with community-acquired Pneumonia, also have reported coinfections in M. pneumoniae as the most common bacteria detected in association with a virus [39]. Thus, to avoid under-diagnosis, pertussis should be considered in patients with cough, especially if chronic, even when M. pneumoniae have been documented [40].…”
Section: Discussionmentioning
confidence: 99%